Comparison of the Effectiveness of Trauma-Focused Cognitive Behavioral Therapy and Acceptance and Commitment Therapy on Self-Efficacy of Adolescents with a History of Domestic Violence - Gholami , Samaneh; Fakhri, Mohammad Kazem; Khalili , Gholamreza (Applied Family Therapy Journal (AFTJ), 2025)
Objective: The aim of this study was to compare the effectiveness of Trauma-Focused Cognitive Behavioral Therapy (TF-CBT) and Acceptance and Commitment Therapy (ACT) on the self-efficacy of adolescents with a history of domestic violence. Methods: The research method was a semi-experimental design with a pre-test–post-test structure and a non-equivalent control group. The study population consisted of 69 adolescent girls, aged 14 to 18 years, who had experienced domestic violence and had a case file at the Social Emergency Center of Babol city during the second half of 2023. A total of 45 participants were selected through convenience sampling based on inclusion criteria and were randomly assigned to two experimental groups of 15 participants each and one control group of 15 participants. Data were collected using the Morris Self-Efficacy Questionnaire (2001). A summary of TF-CBT sessions, adapted from Cohen (2001), consisting of 10 sessions of 90 minutes each, and a summary of ACT sessions, adapted from Hayes et al. (2004), consisting of 8 sessions of 90 minutes each, were administered to the experimental groups. No intervention was applied to the control group. Data analysis was performed using repeated measures analysis of variance (ANOVA) with SPSS 18 software. Findings: The findings indicated that both TF-CBT and ACT had an effect on the self-efficacy of adolescents with a history of domestic violence. However, TF-CBT was more effective than ACT in enhancing self-efficacy. Conclusion: The results of this study could provide practical implications for therapists and counselors.